PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA KEBUN RIMBA BELIAN INTI KABUPATEN SANGGAU - Fatmawati E.01105021, Syarifah (FISIP Universitas Tanjungpura, 2013)
Every leader basically has different behavior in leading or often is called as with leadership style. Human resource stands of vital importance because man as drive wheel from all corporate activity. Strives to increase performance is done with leadership style arranged carefully and giving of motivation that employee performance increases. Purpose of this research is to know leadership style influence of democracy to employee performance.Leader of with good leadership style will create high motivation in x'self every subordinate, so that with the motivation will arise spirit [of] job (activity which can increase performance from the subordinate.This research applies survey method with questionaire as a means of data collecting. Population in this research is all employee PT. Kebun Rimba Berlian Inti which amounts to 18. Sample taken 18 employee with quantitative technique. Data obtained through questionaire tested by validity and reliability by using correlation formula product moment.Result of research indicates that : ( 1) Leadership Style of Democracy influential positive to employee performance PT. Kebun Rimba Berlian Inti. There is relationship and influence between leadership style variables with employee performance at jungle garden belian core showing by correlation coefficient product moment 0,807. Relation between leadership style variable with employee performance at jungle garden belian core is very strong that is with value 0,807. Contribution given by leadership style variable to employee performance is equal to 65%.Â Key Words:Â Democracy Leadership StyleDemocracy Leadership StyleDemocracy Leadership Style, Employee Performance